Radiofrequency magnetic field effects on chemical reaction yields - Stass, D; Woodward, JR; Timmel, C; Hore, P; McLauchlan, K (2000)
The influence of radiofrequency magnetic fields (1-80 MHz) on the yields of radical recombination reactions is investigated. A decrease in the recombination probability of radical ion pairs (monitored via exciplex fluorescence) is detected when the radiofrequency matches energy-level splittings arising from hyperfine interactions in the radicals. The dependence of the oscillating magnetic field effect (OMFE) spectrum on radiofrequency field strength and hyperfine coupling constants is presented for several reaction partners. The experimental studies are supported by theoretical simulations of recombination yields based on the radical pair mechanism (RPM). © 2000 Elsevier Science B.V.